2012
DOI: 10.5301/ejo.5000213
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 6–174G>C Polymorphism in Primary Open-Angle Glaucoma

Abstract: Our findings suggest that the functional IL-6-174G>C polymorphism itself is unlikely a major risk factor for POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Our results are similar to Zimmermann's study in a primary open angle glaucoma group. 5 These results of our study revealed that serum IL-6 value was a borderline higher in NTG patients compared to controls. These results are similar to the results of Huang and colleagues who found that serum levels of IL-6 were higher in POAG patients.…”
supporting
confidence: 57%
“…Our results are similar to Zimmermann's study in a primary open angle glaucoma group. 5 These results of our study revealed that serum IL-6 value was a borderline higher in NTG patients compared to controls. These results are similar to the results of Huang and colleagues who found that serum levels of IL-6 were higher in POAG patients.…”
supporting
confidence: 57%
“…Oh et al [102] showed that human MSCs secrete small amounts of IL-6 and large amounts of TGF-b1 into the culture medium, and this secretion affected the recovery of the apoptotic tissues [102,103]. It has been reported that IL-6 protects retinal ganglion cells from pressureinduced apoptosis, indicating a possible role in the pathogenesis of primary open-angle glaucoma because of its proinflammatory and antiapoptotic effects [104]. The increased level of IL-6 secretion might be explained by the regulation of human MSCs in the co-culture with chemically damaged human corneal epithelial cells [105,106].…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, previous studies have interests in the association between IL-6 polymorphisms and glaucoma including POAG and NTG in different populations. 11,[17][18][19][20] For example, Zimmermann et al reported that the IL-6 rs1800795 polymorphism is unlikely associated with POAG. 18 Lin et al found that the IL-6 rs1800795 polymorphism is not significantly associated with NTG in Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The present study involved four case-control studies [17][18][19][20] with a total of 760 cases and 799 controls, and characteristics of these selected studies are summarized in Table 1. The publication years of these included studies were between 2010 and 2016.…”
Section: The Selection Flow and Characteristics Of Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation